2022
DOI: 10.1016/j.psj.2021.101604
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomics study on the effects of rearing ducks in cages on bone quality

Abstract: The cage rearing model of the modern poultry industry makes the bones of birds more vulnerable to deterioration. In this study, at 8 wk of age, a total of 60 birds were randomly allocated to 2 groups, including the floor rearing group ( FRD ) and cage rearing group ( CRD ), and their body weight was measured every 2 wk. At the age of 20 wk, the tibia, femur, and humerus were collected from each group (n = 12) to determine the bone quality parameters such as weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Yang et al. ( 2022 ) found in Nonghua ducks that the breaking strength, the cortical bone thickness and the percentage of cortical bone area of tibia, femur and humerus, as well as the mineral density and the calcium content of humerus in cage‐reared ducks was significantly lower than those of floor‐reared ducks probably due to higher stocking density and less opportunity to perform locomotory behaviour. Bone quality deterioration in the cage‐rearing system was related to perturbed amino acid, lipid and energy metabolism.…”
Section: Assessmentmentioning
confidence: 99%
“…Yang et al. ( 2022 ) found in Nonghua ducks that the breaking strength, the cortical bone thickness and the percentage of cortical bone area of tibia, femur and humerus, as well as the mineral density and the calcium content of humerus in cage‐reared ducks was significantly lower than those of floor‐reared ducks probably due to higher stocking density and less opportunity to perform locomotory behaviour. Bone quality deterioration in the cage‐rearing system was related to perturbed amino acid, lipid and energy metabolism.…”
Section: Assessmentmentioning
confidence: 99%
“…The health of the Pitalah ducks is highly dependent on the environmental conditions and the participation of Pitalah duck breeders in the care of their livestock [33]. Health management skills are realized through direct activities conducted by Pitalah duck breeders regarding the health of their livestock [34].…”
Section: Healthmentioning
confidence: 99%
“…Bone quality parameters such as bone breaking strength (BBS), bone mineral density (BMD), bone mineral content (BMC), and bone ash content have been utilized to assess the bone status of poultry ( Kim et al, 2006 ; Rubin et al, 2007 ; Li et al, 2020 ; Ma et al, 2020 ), which are affected by the type of housing system ( Regmi et al, 2015 ), genetics ( Guo et al, 2017 ), nutrition ( Ye et al, 2021 ), diseases ( Liu et al, 2021 ), and age ( Sanchez-Rodriguez et al, 2019 ). A recent study indicated that the breaking strength, percentage of the cortical area, and cortical thickness of the tibia, femur, and humerus of ducks raised in a floor system were significantly higher than in cage-reared ducks ( Yang et al, 2022 ). Methods such as dietary changes in the calcium-phosphorus ratio, rearing in a range-free system with more opportunities for walking and flighting, increasing load-bearing exercise, and genetic selection for bone quality have been shown to have positive effects on poultry bone quality parameters ( Dunn et al, 2007 ; Hester et al, 2013 ; Casey-Trott et al, 2017 ; Zhu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%